Perspectives on the current state of Nigeria’s emergency care system among participants of an emergency medicine symposium: a qualitative appraisal - Agnes Usoro; Benjamin Aiwonodagbon; Jonathan Strong; Sean Kivlehan; Babatunde A Akodu; Ayobami Olufadeji (BMJ Open)
Introduction Emergency care systems provide timely and relevant care to the acutely ill and injured. Published commentaries have characterised deficiencies in the Nigerian emergency care system and offered potential solutions but have not included the perspectives of the Nigerian public. A more inclusive approach that includes feedback from the public may help improve the Nigerian emergency care system through better understanding of the needs, values and expectations of the community.Methods Participants of an emergency medicine symposium participated in focus group discussions that were randomly divided into small groups led by two trained facilitators. These facilitators asked open-ended, semistructured questions to lead discussions in the English language. Participant responses were audio-recorded and transcribed verbatim into transcripts. Two independent investigators employed conventional content analysis to code the transcripts until thematic saturation was achieved.Results Three descriptive themes emerged characterising the current state of Nigeria’s emergency care system as it relates to prehospital care delivery, hospital care delivery and health system governance: rudimentary, vulnerable and disconnected. At the prehospital level, concepts revolved around emergency recognition and response, ambulance and frontline providers, and cultural norms. At the hospital level, concepts centred around the health workforce, clinical competency, hospital capacity and the burden of financial hardship. At the health system level, concepts concentrated on healthcare access and healthcare financing. Opportunities for emergency care system improvement at each component level were identified and explored.Conclusions The participants in this study identified shortcomings and opportunities to improve prehospital care, hospital care and health system governance. The results of this study may help healthcare professionals, policy makers and community leaders identify gaps in the emergency care system and offer solutions in harmony with the needs, values and expectations of the community. If successful, these community-informed interventions may serve as a model to improve emergency care systems throughout Africa.